Step
*
1
1
1
1
2
of Lemma
iterate-rotate-rotate-by
1. n : ℕ
2. i : ℤ
3. ¬i < 1
4. 0 < i
5. rot(n)^i - 1 = rotate-by(n;i - 1) ∈ (ℕn ⟶ ℕn)
6. x : ℕn
7. ¬(n = 1 ∈ ℤ)
⊢ (((x + (i - 1) rem n) + (1 rem n) rem n) = ((x + (i - 1)) + 1 rem n) ∈ ℤ)
⇒ (if (x + (i - 1) rem n =z n - 1) then 0 else (x + (i - 1) rem n) + 1 fi 
   = ((x + (i - 1) rem n) + (1 rem n) rem n)
   ∈ ℤ)
BY
{ (RWO "one-rem" 0 THEN Auto) }
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  i  :  \mBbbZ{}
3.  \mneg{}i  <  1
4.  0  <  i
5.  rot(n)\^{}i  -  1  =  rotate-by(n;i  -  1)
6.  x  :  \mBbbN{}n
7.  \mneg{}(n  =  1)
\mvdash{}  (((x  +  (i  -  1)  rem  n)  +  (1  rem  n)  rem  n)  =  ((x  +  (i  -  1))  +  1  rem  n))
{}\mRightarrow{}  (if  (x  +  (i  -  1)  rem  n  =\msubz{}  n  -  1)  then  0  else  (x  +  (i  -  1)  rem  n)  +  1  fi 
      =  ((x  +  (i  -  1)  rem  n)  +  (1  rem  n)  rem  n))
By
Latex:
(RWO  "one-rem"  0  THEN  Auto)
Home
Index